Vacuum-assisted Water Removal from Highly Refined Furnishes - Antti Koponen; Juan Cecchini; Samuli Heiskanen; Merja Selenius; Ari Jäsberg (BioResources, 2023)
A vacuum-assisted sheet former was used for analyzing water removal from refined bleached hardwood kraft pulp furnishes. The Schopper Riegler (SR) values of the studied furnishes ranged from 43 to 97. Water removal time increased significantly with increasing SR value; the water removal time for SR97 furnish was two orders of magnitude longer than for SR43. Retention behaved differently with different SR levels. Retention was approximately constant for SR43 and SR72, for SR85 retention was initially slightly lower, and for SR97 retention was initially very low. The clogging of the wire due to the fines was very strong for SR97. A simple model of flow resistance of the filtered sheet worked very well for SR43 and SR72, and the model worked reasonably well for SR85. However, for higher SR levels, a retention model is needed to predict accurately the water removal in real-life applications.